Hormonal control on repair of ovarian stroma of buffalo caused by follicular atresia - Sharma, G Taru; Majumdar, A C (The Indian Journal of Animal Sciences, 2012)
Histological and immunohistochemical studies were undertaken on atretic follicles of buffalo to observe hormonal regulationon the process of repair of ovarian stroma caused due to follicular atresia. It was noted from the study that at the onset ofatresia of secondary and tertiary follicles, the granulosa cells get disorganized, Â pycnotic and subsequently die makingvacuoles. Thecal cell hyperplasia and hypertrophy occurs and slowly the vacuolar space gets filled. Immunohistochemicalstudies showed LH localization in the inner cell layers of hypertrophied theca whereas prolactin was localized in the outercell layers of such theca. No FSH was localized in the hypetrophied theca. Progesteone was more in the inner layer of cellsthan that of the outer layers. It may be concducted that thecal glands synthesize progesterone under the influence of LH inthe inner cell mass whereas progesterone synthesis or outer cell mass is probably controlled by prolactin. Due to theircombined effect the stromal repair occur, caused due to the follicular atresia.